On the Role of Accent in Ancient Greek Poetry: Pitch Patterns in the Homeric Hexameter - Abritta, Alejandro (2015)
This paper attempts to prove that Ancient Greek tonal accent had a role in the composition of poetry, in particular of Homeric poetry. In order to do this, after a methodological discussion on how to show that accent was indeed taken into account when composing, the author conducts several tests regarding trochaic ending words in the hexameter.